A idéia de saúde, meio ambiente e educação ambiental e alunos do ensino fundamental - Vigia de Nazaré/PA - LIMA, Rosanira Furtado de (2006)
The study represents a contribution to enrich the patrimony of the Teaching of Sciences, starting from professional experiences and people with the theory in the fields of the health, environment and environmental education, in school environment. This study also represents a responsibility in the sense of collaborating with the construction of a formal education that can unmask a critical vision of the social reality. Two research subjects (How students of 5th series of the fundamental teaching express in their ideas the concepts of health, environment and does education adapt and, why is a person's health related with the environment where she lives and, with the environmental education what does she have) were they proposed with the intention of looking for a better understanding in the way how students of the fundamental teaching show in their ideas the enunciation of the concepts of health, environment and environmental education and the relationship among them. The methodological mark points the case study as the knowledge used for the sustentation and materialization of the investigation and, the observation and the interview as necessary complementally knowledge to the accomplishment of the planning, of the collection and of the analysis of the data. The methodological delineate describes of the context in which the subject of the research are inserted, the atmosphere of the research, the construction of the data, the encounter researcher-subjects and the concepts used in the study. The results are shown in two sections. The first display as the subject of the research if they manifested in relation to the concepts of health, environment and environmental education. Monday shows the reason a person's health is related with the environment where she lives and with the environmental education that she has, according to the manifestations of the subject of the research. The study shows a reflection on the theme on the agenda (total knowledge) and the classroom (local knowledge) and. it points that it is possible to build an education school, significant, starting from the knowledge, interests and local needs without losing the dimension macro of the school, of the society and of the world.